ACCEPTABLE ILLUMINANCE LEVEL ATTRIBUTES TO LEARNING SATISFACTION IN CLASSROOM - Fadli, Arabi; Elina, Mohd Husini; Raja Nur Syaheeza, Raja Mohd Yazit; Yakubu Aminu, Dodo; Mohd Zin, Kandar (IRAJ International Journals, 2018)
The importance of student’s satisfaction in school is to highlight the parameter that related to physical of buildings and learning area. Natural lighting is important to human where the daylight shall cause visual discomfort and performance in classrooms. Due to address the issue, the acceptable illuminance level is needing to be identified to increase performance in occupants’ satisfaction. Illuminance level in learning spaces should not be neglected where in the form of human values, comfort and culture are to be focused as a main criterion in student’s performance. Daylighting in an educational space can be improved in order to enhance the student’s performance and promotes a better health and performance due to suitable level of visual comfort. The aim of this study is to investigate the student’s performance in classroom with minimum performance zone in minimum Window-to-Wall Ratio (WWR). The physical conditions; WWR of less than 25%, to 40% of typical of classroom and illuminance level that ranged from 300-400 lux were identified to be sufficient daylight level. Pilot studies have been conducted in typical classroom of KolejPermataInsan where the effects of acceptable illuminance level that contribute to visual performance is identified. Qualitative survey has been conducted on the student’s perception toward visual comfort and obtaining the comparison on performance from visual test. The illuminance level for the classroom was recorded using an LED data logger. Findings from the case study showed less than 20% openings in classrooms affect students minimum acceptable of illuminance level. There will significant contrast between internal luminance to external luminance if WWR is more than 70%. While the ideal WWR for classroom should be not more than 40% to achieve the optimum performance zone and acceptable illuminance level. The findings contribute towards the identification of an acceptable visual comfort ranges for students and design recommendations for optimum performance zone in a classroom in Malaysia.